Quantitatively Decoupling the Relationships Between Discharge and Sediment Yield During Flood Events in China's Loess Plateau - Zelin Li; Guangyao Gao; Anqi Huang; Lishan Ran; Dongfeng Li; Bojie Fu (Water Resources Research)
Abstract To clarify changes of discharge (Q) and sediment yield (SSY) during flood events provide critical insights for flood disaster prevention and control. However, our understanding of the long‐term variations and driving factors of Q‐SSY relationships during flood events remains limited. This study examined the variations in Q, SSY, and sediment rating curves (SSY = aQb) during maximum one, three, and five flood events (ranked by peak discharge) across 15 catchments in the China's Loess Plateau during 1956–2019. We used the partial least squares‐structural equation modeling (PLS‐SEM) to quantitatively decouple the effects of driving factors (precipitation, soil, vegetation, topography, and soil and water conservation measures (SWCMs)) on Q‐SSY relationships. There was a significant declining trend in both Q and SSY during flood events across catchments, but their contributions to annual SSY significantly increased by 41.48%, underscoring the critical role of floods in sediment transport. The Q‐SSY relationship during flood events became weakened over time, with coefficient a decreased and index b increased. The five driving factors explained 44%–49% of the changes in coefficient a and 36%–51% in index b. Significant direct effects of vegetation (path coefficient (β) = −0.921) and precipitation (β = 0.616) on coefficient a were observed (p < 0.05). Index b was principally dominated by SWCMs and vegetation, and the effects diminished with increase in number of flood events. These findings highlight the importance of vegetation cover and SWCMs in mitigating sediment transport, offering valuable insights for sediment management strategies in the Loess Plateau and similar regions.